Efficacy of some metronidazole derivatives against Giardia lamblia, in vivo study - Mohammad Hossein Motazedian; Nilofar Mohammadpour; Soghra Khabnadideh (Shiraz University of Medical Sciences, 2015)
Giardiasis is a protozoal infection of small intestine caused by Giardia lamblia. This disease is usually asymptomatic, though it can present as acute or chronic diarrhea. Giardiasis, which is a major cause of intestinal infection, is endemic in Iran. Despite reports about drug resistance, long course treatment and various side effects of metronidazole, it is the drug of choice for giardiasis. In this study, we investigated the in vivo effects of five new derivatives (a-e) of metronidazole (MTZ) on the Giardia lamblia trophozoite in infected mice. Giardia intestinalis cysts were isolated from a patient and purified by sucrose gradient method. Fifty purified cysts were fed to the mice. After development of infection, the new metronidazole derivatives were given to the mice and the results were compared with metronidazole as the positive control group. Compounds a and b showed desirable antigiardiasis activity and could destroy the cyst and trophozoite of Giardia lamblia in mice after both two and four days, but the activity of the other compounds appeared only after 4 days.